Usulan Pengelolaan Sampah di Kelurahan Margasari Kota Bandung Menggunakan Pemodelan Dinamika Sistem - Miftahuljanah, Winna; Didit Damur Rochman (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2024)
Kelurahan Margasari in Bandung West Java, located at Jalan Cipagalo Girang No. 9. Covering an area of 272.18 hectares, Margasari is the largest kelurahan in the kecamatan Buah Batu, accounting for 37% of its total area. Margasari is among the kelurahan that generate substantial waste, originating from household and business activities. The research aims to identify waste flow in kelurahan Margasari and propose waste management strategies to reduce waste generation based on system dynamics simulation results. A quantitative approach employing system dynamics methodology is utilized. Simulations encompass three scenarios: Scenario 1 represents the baseline, Scenario 2 involves waste sorting with 100% organic waste recycling and proportional distribution of inorganic waste, while Scenario 3 incorporates waste sorting with 100% organic waste remaining untreated and 100% inorganic waste processed. Over a 1,000-day simulation period, Scenario 3 exhibits the lowest waste amount deposited in the landfill, totaling 4,813.28 kg/day. This reduction is attributed to the full segregation of inorganic waste. Thus, maximizing waste sorting in kelurahan Margasari proves to be the most effective approach in minimizing landfill waste. Model validation confirms the applicability of system dynamics in analyzing interrelated factors crucial for sustainable waste management planning